2000
DOI: 10.1063/1.1290478
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of capillary evaporation. I. Effect of morphology of hydrophobic surfaces

Abstract: Cavitation has been suggested to be a possible source of long range interactions between mesoscopic hydrophobic surfaces. While evaporation is predicted by thermodynamics,little is known about its kinetics. Glauber dynamics Monte Carlo simulationsof a lattice gas close to liquid-gascoexistence and confined between partially drying surfacesare used to model the effect of water confinement on the dynamics of surface-inducedphase transition. Specifically, we examine how kinetics of induced evaporation change as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
137
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 72 publications
6
137
0
Order By: Relevance
“…Concerning self-diffusion, it is easier at the vicinity of hydrophobic interfaces. Recent studies have shown that a layer of water vapour exists at the vicinity of hydrophobic surfaces (Mezger et al 2006) confirming also different results obtained by simulations of the molecular dynamics (Luzar and Leung 2000). Also, it was observed that the dynamics of hydration water is different in the case of peptides that differ only by the presence of a hydrophobic chain in the first case as shown in the cases of N-acetyl-leucine-methylamide and N-acetyl-glycinemethylamide (Russo et al 2008).…”
Section: Resultssupporting
confidence: 67%
“…Concerning self-diffusion, it is easier at the vicinity of hydrophobic interfaces. Recent studies have shown that a layer of water vapour exists at the vicinity of hydrophobic surfaces (Mezger et al 2006) confirming also different results obtained by simulations of the molecular dynamics (Luzar and Leung 2000). Also, it was observed that the dynamics of hydration water is different in the case of peptides that differ only by the presence of a hydrophobic chain in the first case as shown in the cases of N-acetyl-leucine-methylamide and N-acetyl-glycinemethylamide (Russo et al 2008).…”
Section: Resultssupporting
confidence: 67%
“…[13][14][15] It has also been possible to study the dynamical behavior for such models through the use of dynamic Monte Carlo simulations with Kawasaki dynamics, which models dynamics generated by nearest neighbor hopping processes. Examples include phase separation dynamics for confined liquid mixtures, 10,11 the kinetics of nonwetting liquids in pores, 16,17 and the relaxation dynamics during gas adsorption in porous glasses. 15,18 These approaches are an efficient alternative to very time consuming nonequilibrium molecular dynamics calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation examples of such confinement-induced drying (50) range from nanotubes (51) to plates (28,45,(52)(53)(54)(55)(56)(57)(58)(59) and the interfaces between proteins (30,60) to collapsing polymers (25)(26)(27). Associated with these surface-induced drying transitions are nanometer-scale fluctuations in the local water density (27), resulting in detectable locally liquid-like and vapor-like phases.…”
Section: Discussionmentioning
confidence: 99%